2015
DOI: 10.1111/zoj.12286
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable ancient divergences amongst neglected lorisiform primates

Abstract: Lorisiform primates (Primates: Strepsirrhini: Lorisiformes) represent almost 10% of the living primate species and are widely distributed in sub‐Saharan Africa and South/South‐East Asia; however, their taxonomy, evolutionary history, and biogeography are still poorly understood. In this study we report the largest molecular phylogeny in terms of the number of represented taxa. We sequenced the complete mitochondrial cytochrome b gene for 86 lorisiform specimens, including ∼80% of all the species currently reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
55
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 88 publications
4
55
0
Order By: Relevance
“…Molecular data indicate that some diversification may have occurred within Nycticebus (slow lorises) during the Pliocene (Pozzi et al 2015). Galagos (family Galagidae), however, do have a Pliocene fossil record, and are found at several African sites familiar to students of human evolution, such as Omo (Shungura Formation), Laetoli (Upper Laetolil Beds), and Kanapoi.…”
Section: Lemurs and Lorisesmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular data indicate that some diversification may have occurred within Nycticebus (slow lorises) during the Pliocene (Pozzi et al 2015). Galagos (family Galagidae), however, do have a Pliocene fossil record, and are found at several African sites familiar to students of human evolution, such as Omo (Shungura Formation), Laetoli (Upper Laetolil Beds), and Kanapoi.…”
Section: Lemurs and Lorisesmentioning
confidence: 99%
“…Material represents two extinct species, Galago sadimanensis and Otolemur howelli. According to DNA evidence, one extant galago genus, Sciurocheirus (squirrel galagos), originated in the Pliocene (the rest emerged in the Late Miocene; Pozzi et al 2015).…”
Section: Lemurs and Lorisesmentioning
confidence: 99%
“…The crown strepsirrhine lineage has African roots dating back to the late Eocene (about 40 Mya), and split into one galagine and two lorisine lineages shortly thereafter (about 38 Mya) (Seiffert et al, 2003;Pozzi et al, 2015). One lorisine lineage remained in tropical Africa with the galagines, the other migrated north out of Africa and into Asia by way of temporary Afro-Arabian land bridges (Masters et al, 2005).…”
Section: The "Out Of Asia" Hypothesis For the Origin Of Indian And Srmentioning
confidence: 99%
“…Within the taxon, N. coucang, which is endemic to Sumatra, the Malaysian Peninsula and several islands within the South China Sea and the Malacca Straits, diverged from N. menagensis, endemic to Borneo, Natuna and the Philippines, during the Pliocene approximately 6 million years later [Groves, 1971;Groves and Maryanto, 2008]. According to molecular phylogenetics, evidence suggests that Lorisidae is the most genetically divergent group of primates [Perelman et al, 2011], and Nycticebus is recognised as the most diverse lorisid genus [Pozzi et al, 2015]. Therefore, isolation of Nycticebus populations as a consequence of rising sea levels at the end of the Pleistocene epoch is likely to have culminated in further diversification of extant species.…”
Section: Introductionmentioning
confidence: 99%
“…Substantial variation in morphological traits exhibited amongst slow lorises has been well documented [Nekaris and Jaffe, 2007], yet analysing morphological variation between specimens has likely failed to identify previously unrecognised species amongst known and isolated populations, partly owing to small sample sizes. Welch DOI: 10.1159/000499655 Recent phylogenetic research has shown that the Nycticebus genus first originated approximately 11 million years ago [Pozzi et al, 2015]. Although slow loris evolutionary biogeography is poorly understood, Nycticebus inhabited the Sundaland islands before sea levels rose [Groves, 1971].…”
Section: Introductionmentioning
confidence: 99%